PERINATAL BRAIN INJURY: CURRENT ISSUES OF EPIDEMIOLOGY AND APPROACHES TO CLASSIFICATION - D. V. Blinov (Акушерство, гинекология и репродукция)
Perinatal brain ingury including hypoxic-ischemic encephalopathy (HIE) is serious problem of healthcare. Data on HIE prevalence in Russia is quite heterogeneous. Generally, prevalence in Russia is higher than in developed countries. The article presents the existing data on the prevalence of HIE in Russia, modern approaches to definition and classification. Large-scale studies and register could be helpful for further verification of the prevalence, incidence, outcomes and other measures. It is also important to further systematization of criteria for the diagnosis of perinatal CNS lesions. The usage of common approaches in routine practice, such as the RASPM classification, Sarnat classification, Levene classification would be helpful for epidemiological studies and for unifying approaches to the management of patients in order to prevent over-diagnosis and ensure proper choise of treatment.